A comprehensive review on production, surface modification and characterization of nanocellulose derived from biomass and its commercial applications - R. Kumar; B. Rai; S. Gahlyan; G. Kumar (eXPRESS Polymer Letters, 2021)
The demand for exploring eco-friendly and advanced materials for sustainable development with exceptional physicochemical properties is increasing day by day. Recently, nanocellulose in its all form such as cellulose nanocrystal, cellulose nanofibers, and bacterial cellulose gain great attention in both research and industrial areas due to their appealing inherent properties such as excellent mechanical properties, high concentration of hydroxyl groups for modification, high surface area, lightweight, and biodegradability. However, the hydrophilic nature of nanocellulose restricted its utilization in various applications, but the presence of a functional group on its surface provides a platform for surface modification through various techniques. In this review, the source of nanocellulose, a brief description of the chemical structure of nanocellulose, its type, typical production methods, surface modification, and general application such as textile, biomedical fields, wastewater purification, food packaging are summarized. It is expected to provide broad knowledge about the usefulness of present and future perspectives of nanocellulose for the benefit of the environment and society.